SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) UNTUK MENINGKATKAN KUALITAS HIDUP PADA WANITA YANG MENGALAMI BENCANA TANAH LONGSOR - Aftrinanto, Zuhdan; Hayati, Elli Nur Nur; Urbayatun, Siti (Faculty of Ushuluddin and Humanities, 2018)
Spiritual Emotional Freedom Technique (SEFT) is engineering the merger of the energy system of the body and spirituality therapy using the method of tapping on certain points on the body. The purpose of this study was to determine the influence of Spiritual Emotional Freedom Technique in improving the quality of life in women who experienced landslide disaster in Purworejo. This study uses a quasi-experimental design with one group pretest-posttest design research model. The subjects of this study were six women in Purworejo with criteria aged 20 to 40 years, experienced landslide disaster, and having a low quality of life based on WHOQOL-BREF scale categorization. The experimental group was treated using the Spiritual Emotional Freedom Technique therapy. Quantitative data analysis techniques using Wilcoxon Signed Rank Test analysis. Qualitative data analysis is obtained from the observation, interview, worksheet, and evaluation sheet. The results showed that there was a significant increase in quality of life, both in each domain and overall between before and after being treated by SEFT. Based on that results, it can be concluded that the SEFT (Spiritual Emotional Freedom Technique) can improve the quality of life of women who experienced a landslide disaster in Purworejo.